Analisis Pengaruh Fungsi Manajemen terhadap Efektivitas Lembaga Pendidikan - Fadiah Nur Amalia; Fadhila, Fadhila; Kezia Nur Elizanti Purba (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This research aims to evaluate the influence of management functions on the effectiveness of educational institutions through a qualitative approach using a literature review method. By focusing on planning, organizing, directing and monitoring, this research identifies the relationship between management functions and aspects of the effectiveness of educational institutions. The data collection process involved a systematic search of online library sources with relevant keywords, followed by selection and in-depth analysis of the selected sources. Through critical analysis, this research aims to produce insights that are useful for the development of educational management science and practical implementation in improving the performance of educational institutions. It is hoped that the findings of this research can be a valuable contribution for stakeholders in the education sector in an effort to increase the effectiveness of the management of educational institutions.